2008
DOI: 10.1002/ejoc.200700684
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and Intramolecular C–H···O Bonding in the Anions of 1,3‐Indandione Derivatives

Abstract: Derivatives of a series of 1,3-indandione (1) self-condensation products (2-4) and their anions (2a-4a) were investigated by NMR and UV/Vis spectroscopy and quantum mechanical calculations. These compounds exhibit a number of unusual features in their NMR spectra. Parent compound 1 is nearly not ionized in DMSO, whereas 3 is ionized completely. In contrast, derivatives 2 and 4 undergo partial ionization in DMSO and interaction between the neutral and anionic species affords the anionic intermolecular complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…To probe the cage-based catalysis of this reaction, we first examined the pH profile of the uncatalysed 'background' reaction, looking for conditions where this was as slow as possible to allow the effects of any catalysis to be most apparent. Monitoring the formation of bindone by UV/Vis spectroscopy (it has a strong absorption maximum at 510 nm in water) [44] at a range of different pH values showed that the reaction proceeds quickest in the pH range 6-7 where, based on the pKa of the starting material, there will be substantial amounts of both nucleophilic enolate anions and electrophilic neutral ID present; the reaction becomes slower at greater extremes of high or low pH. To facilitate the analysis of the reaction by UV/Vis spectroscopy, we therefore performed our subsequent experiments in the range of pH 3-4, reasoning that-as with the Kemp elimination reactions we examined earlier [29,30]-the high positive charge of the cage should stabilise the anionic enolate form of ID, even under relatively acidic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To probe the cage-based catalysis of this reaction, we first examined the pH profile of the uncatalysed 'background' reaction, looking for conditions where this was as slow as possible to allow the effects of any catalysis to be most apparent. Monitoring the formation of bindone by UV/Vis spectroscopy (it has a strong absorption maximum at 510 nm in water) [44] at a range of different pH values showed that the reaction proceeds quickest in the pH range 6-7 where, based on the pKa of the starting material, there will be substantial amounts of both nucleophilic enolate anions and electrophilic neutral ID present; the reaction becomes slower at greater extremes of high or low pH. To facilitate the analysis of the reaction by UV/Vis spectroscopy, we therefore performed our subsequent experiments in the range of pH 3-4, reasoning that-as with the Kemp elimination reactions we examined earlier [29,30]-the high positive charge of the cage should stabilise the anionic enolate form of ID, even under relatively acidic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We report here that our cage system can catalyse an aldol reaction: the conversion of indane-1,3-dione to bindone (Scheme 1) [43][44][45][46]. This was discovered by accident when we were evaluating the binding constants of a range of possible guests using spectroscopic titrations in solution; the addition of indane-1,3-dione (abbreviated hereafter as ID) to an aqueous solution of H w resulted in the gradual appearance of a purple colour, which interfered with the titration experiment, but signalled the formation of the condensation product bindone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) kept at room temperature leads to the formation of small domains poorly ordered (Supplementary Fig. 2) whereby the intermolecular cohesion is ensured by a dense network of hydrogen bonds505152. The subsequent surface annealing or direct molecule deposition on a substrate held at a slightly elevated temperature (50 °C) fosters the growth of extended two-dimensional (2D) highly ordered molecular islands with two chiral domains, as shown in the large-scale STM image and corresponding low-energy electron diffraction (LEED) pattern of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to 1 H and 13 C NMR spectroscopic data, 1,3-indanedione exists in the diketo form even in DMSO. [5] However, substitution of the parent molecule may significantly affect the tautomeric equilibrium. For example, 2-phenyl-1,3-indanedione was the first compound for which the existence of the enol form was postulated about a century ago.…”
Section: Introductionmentioning
confidence: 99%